Pengaruh Penggunaan Media Teks Berjalan Terhadap Kemampuan Membaca Pemahaman Teks Berita Pada Siswa Kelas VII SPMN 1 Kota Sukabumi Tahun Ajaran 2023/2024 - Putri Awalia, Shalma; Wahdah Humaira, Hera; Suparman, Fauziah (Universitas Tidar, 2024)
This research aims to determine the effect of using walking text media on the ability to read and understand news texts. The research method used is quantitative research using a Pre-Experimental Design One Group Pretest-Posttest Design research design. The data collection technique in this research is a test. The research instrument used in this research is an objective test in the form of a multiple choice of 20 questions which will be carried out twice, namely during the pre-test and post-test after being given treatment. The sample used by researchers was a purposive sampling technique. The sample in this research was 30 students of class VII K, SMPN 1 Sukabumi City for the 2023/2024 academic year.The results of the research showed that the students' pretest had an average result of 75.83, when they were given treatment using running text media, the students' scores changed when they were given the posttest, namely 89, which means that the students' scores increased after being given treatment. There is a difference between these two values. The tcount > ttable value has been consulted with a significance level of 0.05 and degrees of freedom (d) 23. In this study the tcount value was 10.69 and the ttable value was 2.045. Thus, the use of running text media can influence the ability to read and understand news texts in class VII students at SMPN 1 Sukabumi City. Based on the research results, it is hoped that it will become a reference or reference source in choosing media applications that are appropriate to the learning material and learning objectives to be achieved.